Sanksi Hukum terhadap Hakim Adhoc Pelanggar Kode Etik Profesi Hakim - Ratna Sayyida; Suwari Akhmaddhian (Universitas Kuningan, 2020)
The purpose of this research is to find out how the code and conduct guidelines are set for judges and how to apply sanctions due to violations of the Code of Profession Ethics. The method of research used is normative, which is the method of approach by reviewing the laws that are conceptualized as the norm or the rules that apply to the community, and become the reference of everyone's behaviour. Data collection tools through library studies. Secondary use, i.e. data obtained through documentation studies by reading scientific books, magazines, internet, newspapers and other readings related to research. The results of the research are the settings regarding the code of ethics and the conduct of the judges as legal profession where the judges have obligations of liability or legal responsibility. So that all his deeds are supervised by law. Therefore, in his profession the judges must be neutral and will be the self-esteem and dignity of the judges so that the code of conduct and conduct of the judges can run properly Keywords: ethics; Law; Judge; Profession; Obligation. AbstrakTujuan penelitian ini adalah untuk mengetahui Bagaimanakah pengaturan kode etik dan pedoman perilaku bagi hakim dan bagaimana penerapan sanksi akibat pelanggaran kode etik profesi hakim. Metode penelitian yang digunakan adalah yuridis normatif, yaitu metode pendekatan dengan mengkaji hukum yang dikonsepkan sebagai norma atau kaidah yang berlaku dalam masyarakat, dan menjadi acuan perilaku setiap orang. alat pengumpul data melalui studi kepustakaan. yang digunakan sekunder, yaitu data yang diperoleh melalui studi dokumentasi dengan cara membaca buku-buku ilmiah, majalah, internet, surat kabar dan bacaan-bacaan lain yang berhubungan dengan penelitian. Hasil penelitian yaitu Pengaturan mengenai Kode etik dan pedoan Perilaku Hakim sebagai Profesi Hukum dimana hakim mempunyai kewajiban kewajiban atau tanggung jawab hukum. Sehingga segala perbuatannya diawasi oleh hukum. Karena itu, dalam profesinya hakim harus bersifat netral dan menjungjung harga diri dan martabat hakim sehingga Kode Etik dan Pedoman Perilaku Hakim bisa dijalankan dengan semestinya Kata Kunci : etika; hukum; hakim; profesi; kewajiban.